PERLINDUNGAN HUKUM TERHADAP JURNALIS DALAM MERAHASIAKAN IDENTITAS PELAKU PENGATURAN SKOR DALAM PERTANDINGAN SEPAK BOLA - Farhan, Faisal; Mardijono, HR. Adianto (Gapenas Publisher, 2023)
There are many ways for a country to advance the potential that exists in that country, with the existence of various sports it also makes a new breakthrough to advance a country, one of which is football which is one of the country's priorities in showing the identity of the nation's children at the national and international levels. Internationally, therefore this sport must have clear rules. The presence of a government institution / federation, namely the Indonesian Football Association, has an important role in regulating and making rules for the sport of national football, and PSSI's role is not only to regulate and make rules but also to oversee each club so that they can develop and have integrity. It is possible that in every country there are problems regarding national football standards, this is if you look at the world of Indonesian football where these problems exist and are very present among the people, namely the existence of score fixing which is suspected to have been carried out by the owners of football clubs in Indonesia. . This becomes an interesting matter for the press or journalists in conducting interviews or investigating who is behind fixing the score in a football match. Thus there was an interview where it was alleged that the person was taking part in setting the score, so that this became a matter of great importance and a problem for the state to eradicate who was behind fixing the score, the press or journalists became pros and cons among the public and the government to reveal who the people were involved or who were the perpetrators in fixing the score, hereby according to the government or the federation this is a matter or a serious problem to carry out an investigation in order to reveal who the perpetrators were